Search for hep solar neutrinos and the diffuse supernova neutrino background using all three phases of the Sudbury Neutrino Observatory - Aharmim, Bassam; Ahmed, S. N.; Anthony, A. E.; Barros, N.; Beier, E. W.; Bellerive, A.; Beltran, B.; Bergevin, M.; Biller, S. D.; Blucher, E.; Bonventre, R.; Boudjemline, K.; et al. (Physical review, 2020)
A search has been performed for neutrinos from two sources, the hep reaction in the solar 𝑝⁢𝑝 fusion chain and the 𝜈𝑒 component of the diffuse supernova neutrino background (DSNB), using the full dataset of the Sudbury Neutrino Observatory with a total exposure of 2.47 kton−years after fiducialization. The hep search is performed using both a single-bin counting analysis and a likelihood fit. We find a best-fit flux that is compatible with solar model predictions while remaining consistent with zero flux, and set a one-sided upper limit of Φℎ⁡𝑒⁢𝑝<30×103 cm−2 s−1 [90% credible interval (CI)]. No events are observed in the DSNB search region, and we set an improved upper bound on the 𝜈𝑒 component of the DSNB flux of ΦDSNB𝜈𝑒<19 cm−2 s−1 (90% CI) in the energy range 22.9 <𝐸𝜈 <36.9 MeV.